Pengaruh Struktur Modal Struktur Aktiva dan Likuiditas terhadap Profitabilitas pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia - Anggraini, Nur Fatmawati; Istiatin, Istiatin; Hartono, Sri (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
The purpose of this research is to describe the effect of financial structure, asset composition, and liquidity level on the profits of manufacturing companies listed on the Indonesia Stock Exchange. Over a period of 24 months, 78 companies in the manufacturing sector suffered losses due to sampling. It was successfully studied that the impact of asset structure on profitability was not significant, the impact of capital structure on real profitability, and liquidity had a significant impact on manufacturing companies based on this study. Keywords: Capital Structure, Asset Structure, Liquidity, Profitability